Analisis Perbandingan Metode Trapesium, Simpson 1/3, dan Simpson 3/8 Berbasis Spreadsheet menggunakan Microsoft Excel untuk Aproksimasi Integral Numerik - Rahma Qudsi; Alzaber; Muhammad Rasyid Ridho (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study analyzes the comparison of the Trapezoidal, Simpson 1/3, and Simpson 3/8 to approximate numerical integration using Microsoft Excel, with the variation of the interval . The test function is on the interval . Because it is smooth and lacks an elementary antiderivative, the results indicate that the Simpson Method outperforms the Trapezoidal method in accuracy. The Trapezoidal method yields absolute errors on the order of to , while Simpson 1/3 and 3/8 achieve to , with Simpson 1/3 performing best across all . These findings confirm the higher convergence order of Simpson methods ) vs . Excel implementation proves effective as an accessible learning tool for numerical methods, supporting integral computation in higher education. This research contributes to simplifying computational approaches for engineering applications and education, and opens up opportunities for more effective implementation of numerical methods in practical teaching. The results of this research are expected to enrich understanding of numerical applications in engineering and science.